1994
DOI: 10.1104/pp.105.4.1409
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NaCl on Flows of N and Mineral Ions and on NO3- Reduction Rate within Whole Plants of Salt-Sensitive Bean and Salt-Tolerant Cotton

Abstract: l h e effects of NaCl on the transport rates of cations, NO3-, and reduced N compounds between roots and shoot and on NOsassimilation rate were examined on plants of two species differing in their sensitivity to salinity, bean (Phaseolus vulgare 1 . cv Cabriella) and cotton (Gossypium hirsutum l. cv Akala). Biomass production after 20 d in response to 50 and 100 mM NaCl decreased by 48 and 59% in bean, but only 6 and 14% in cotton. The comparison of the flow patterns obtained for control and NaCIfed plants sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
7

Year Published

1998
1998
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(79 citation statements)
references
References 30 publications
4
68
0
7
Order By: Relevance
“…The decrease noted in NRA was positively correlated to the decrease of leaves' nitrate contents and that could be the cause of the NRA reduction. Indeed, Gouia et al (1994) noted that NRA was not sensitive to osmotic effects.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease noted in NRA was positively correlated to the decrease of leaves' nitrate contents and that could be the cause of the NRA reduction. Indeed, Gouia et al (1994) noted that NRA was not sensitive to osmotic effects.…”
Section: Discussionmentioning
confidence: 99%
“…There were fewer bolls per plant and a greater chance of shedding under the high soil salinity treatment (SH), which might be attributed to the nutrient imbalance caused by high soil salinity. Gouia et al (1994) reported that high salt stress results in slower growth and even death of seeding cotton, lower dry matter accumulation, less Fig. 2 roots, softer and darker leaves, shorter period of blooming, and even death of seedling cotton.…”
Section: Discussionmentioning
confidence: 99%
“…Effect of increasing Na/K ratio in solution on mineral uptake, N transport to the shoots and growth of plants Numerous studies have revealed that salinity stress inhibits nitrate (NO 3 ) uptake and transport to the shoot in both glycophytes and halophytes (Gouia et al 1994;Rubinigg et al 2003). An increase in NO 3 supply can ameliorate salinity stress (Liu et al 2004;Ding et al 2010).…”
Section: Effect Of Increasing Na/k Ratio In Solution On Water Uptake mentioning
confidence: 99%